Новые экономнолегированные литые стали для корпусов буровых коронок - Богаченко, А.Г.; Линенко-Мельников, Ю.П.; Мельник, В.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The technology of producing the sparsely-alloyed steels capable to quenching at a delayed cooling, has been developed on the basis of electroslag crucible melting of used drill bits. The new steels were tested in the production of cast bodies of drill bits.